2008
DOI: 10.1245/s10434-008-0149-y
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Tumor Regression Grade Correlates with Survival in Locally Advanced Rectal Carcinoma Treated with Neoadjuvant Chemoradiotherapy

Abstract: Tumor regression grade measured on a 3-point system predicts outcome after chemoradiotherapy and surgery for locally advanced rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
85
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 39 publications
10
85
0
2
Order By: Relevance
“…In this study, we decided to adopt a three-point classification system (TRGp2, TRG 3 and TRGX4) to split the patients into subgroups with significantly different prognosis, according to previous studies. 13 Two genetic markers were discovered to significantly discriminate between good (TRGp2) and poor (TRGX4) responders, whereas none of the analyzed polymorphisms was able to identify intermediate TRG 3 responders, though a significant trend was found among the three groups by the w 2 test. This exploratory finding could support a borderline situation of these patients either from a histo-pathologic or from a prognostic point of view, although further confirmatory studies could better elucidate this topic.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this study, we decided to adopt a three-point classification system (TRGp2, TRG 3 and TRGX4) to split the patients into subgroups with significantly different prognosis, according to previous studies. 13 Two genetic markers were discovered to significantly discriminate between good (TRGp2) and poor (TRGX4) responders, whereas none of the analyzed polymorphisms was able to identify intermediate TRG 3 responders, though a significant trend was found among the three groups by the w 2 test. This exploratory finding could support a borderline situation of these patients either from a histo-pathologic or from a prognostic point of view, although further confirmatory studies could better elucidate this topic.…”
Section: Discussionmentioning
confidence: 98%
“…Patients were split into three groups expected to have a significantly different therapy outcome on the basis of their TRG. According to literature data, 13,25 patients with TRG 1-2 were considered as good responders, those with TRG 3 were considered as intermediate responders, whereas patients with TRG 4-5 were considered as non-responders. The association between patients' clinico-pathological and demographic characteristics and genotypes and TRG was tested first by univariate Fisher's exact test and by w 2 test for trend.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 A tumor regression grade was assessed using a three-tier classification method. 28,29 For the purposes of this study, pre-treatment rectal biopsies were retrospectively reviewed for evidence of intratumoral budding through a  4 lens, (  40 magnification) with confirmation of positive cases at  10 (  100 magnification) according to the method described by Giger et al, 19 adapted from the Nakamura method of identifying peritumoral budding. 30 Intra-tumoral budding was defined as a single cancer cell or a group of o5 detached tumor cells found in the stroma of the biopsy specimen.…”
Section: Histopathological Stagingmentioning
confidence: 99%
“…Patients with pCR [6,8,16,18,[26][27][28] and those with good tumor regression even in the absence of pCR [8,16,17,21,26,[28][29][30][31] have been reported to have good outcomes. Agarwal et al [28] studied 251 patients with locally advanced rectal adenocarcinoma who received preoperative CRT and found that recurrence-free survival did not differ between patients with pCR and those with nearly complete response (residual cancer cells ≤ 5%).…”
Section: Discussionmentioning
confidence: 99%